Strengthening Food Security and Community Independence: A Community Empowerment Strategy in MSMEs and Halal Food Products from a Legal Perspective in Lempuyang Village, Tanara, Serang - Palmawati Tahir; Muhamad Muslih; Fachrian Luthfi Fadillah; Najla Tasya Fairuz; Raden Prasetio Kustiandrana; Febianca Azania Kholida; Siti Rahmah Arbai; Liyola Wendysofynia (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Kuliah Kerja Mahasiswa (KKM) is an integrated community service activity that involves students as participants and lecturers as supervisors that focus on the theme of entrepreneurship. The type of method used is a qualitative method. There are several stages of activities carried out namely the preparation stage, the assessment stage and the planning stage. The conclusion from the results of legal socialization activities regarding Halal products and UMKM, that based on the data of residents who have not worked is quite high, this can be overcome by being able to start a micro / small scale business to be able to help the family economy and of course with interesting creative ideas to get profits